The good, the bad, and me in my anecdotage - Wallach, Eli 1915-2014 (Harcourt, 2005)
The author recounts his early years in Brooklyn, struggles to become an actor, work with such stars as Marlon Brando and Marilyn Monroe, and role as one of the earliest members of the famed Actors Studio.
Keywords: Wallach, Eli -- 1915-; Wallach, Eli -- 1915-2014; Actors -- United States -- Biography; USA; Autobiografie